Methods and logistics of a multidisciplinary survey of schoolchildren from Pelotas, in the Southern Region of Brazil - Marília Leão Goettems; Marcos Britto Correa; Fabiana Vargas-Ferreira; Dione Dias Torriani; Margarete Marques; Marlos Rodrigues Domingues; Pedro Curi Hallal; Flávio Fernando Demarco (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
This paper describes the methods of a multidisciplinary epidemiological survey conducted in schools in Pelotas, in the Southern Region of Brazil. This cross-sectional study evaluated a representative sample (n = 1,211) of eight to 12-year-old children attending public (15) and private (5) schools. Questionnaires were applied to parents to obtain information about socioeconomic and sociocultural characteristics. Children were interviewed to provide information on demographic characteristics, oral health behavior and physical activity habits. Oral health examinations were performed on the children and anthropometric data was collected to assess nutritional status. School principals responded a questionnaire about the social and physical environment of the school. A total of 1,744 children were eligible for the study; a response rate of 69.4% was achieved, with no significant differences between schools. The method used allowed investigators to obtain data on several health outcomes as well as on possible risk factors. This strategy optimizes the use of financial resources for research and promotes interprofessional collaboration.